Efficacy of atropine for myopia control in children: A meta-analysis of randomized controlled trials - Shalini Kumari; Raj Anand; Shashank Tripathi; Rajesh C Mishra; Simant Kumar Jha (Journal of Family Medicine and Primary Care, 2022)
Objective: To conduct a meta-analysis of randomized controlled trials (RCTs) on the effects of atropine eye drop in slowing myopia progression. Methods: A systematic search of relevant articles was done through a computerized search on PubMed, Medline, Cochrane Library, and Google Scholar on June 16, 2022. A supplementary search was done on ClinicalTrials.gov on the same date. After thorough search and analysis, seven relevant RCTs, double-masked with atropine eye drop as intervention arm and placebo as control arm, were selected for meta-analysis. Jadad scoring was used to evaluate the quality of RCTs. The outcome measurements included in the present meta-analysis are mean changes in the spherical equivalent (SE) of myopic error, and mean changes in axial length (AL) during the study period. Result: Pooled summary effect size, calculated by random effect model, for SE of myopia progression was 1.08 with 95% confidence interval (CI) (0.31–1.86) which was statistically significant (P-value = 0.006). Pooled summary effect size, calculated by random effect model, for axial length was − 0.89 with 95% CI (−1.48 to − 0.30) which was statistically significant (P-value = 0.003). Conclusion: In summary, atropine was demonstrated to be effective in controlling myopia progression in children. Both outcome measures, mean SE changes and mean AL elongation responded to atropine intervention compared to placebo.